FEATURES OF THE SYSTEM OF VALUE ORIENTATIONS OF PSYCHOLOGY STUDENTS IN THEIR FIRST AND FOURTH YEARS - Гордієнко, Наталія; Проскурка, Наталія (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article examines the peculiarities of the value orientation system of psychology students, its impact on their professional activity, and opportunities for developing these values in the learning process. The study of these changes is particularly important for psychology students, as they are future specialists who will play a key role in overcoming the psychological consequences of war and rebuilding the country. In wartime, values such as patriotism, civic responsibility, empathy, and willingness to help become increasingly relevant. The aim of the study was to examine the impact of professionalization (comparison of 1st and 4th year students according to the system of value orientations using M. Rokich’s methodology). The results showed that in the hierarchy of thermal values (life goals) for both groups, “health” and “love” dominate, emphasizing the priority of personal well-being and relationships in times of crisis. However, significant differences were identified: first-year students highly value creativity, while for fourth-year students this value is relegated to the bottom of the list. In terms of instrumental values (means of achieving goals), first-year students emphasize “honesty,” “independence,” and “cheerfulness,” while fourth-year students emphasize “education,” “self-control,” and “good manners.” This shift in priorities indicates the influence of the educational process and professional training, where senior students value the qualities necessary for effective psychological work. Thus, the study confirms that in the context of war and professional training, there is a dynamic change in the value orientations of psychology students. These changes are important for their future as specialists who will work on the psychological recovery of society. Further scientific work should focus on studying the influence of external circumstances, especially war, on the formation of young people’s life priorities.